Direct Coagulation Casting of Alumina Suspension via Controlled Release of High Valence Counterions from Thermo‐sensitive Liposomes. Issue 1 (2nd November 2012) - Yang, Jinlong; Xu, Jie; Wen, Ning; Qu, Yanan; Qi, Fei; Xi, Xiaoqing; Krell, A.
<x xml:space="preserve">Abstract</x> Thermo‐sensitive liposomes were prepared using reverse phase evaporation method using natural lipid egg phosphatidylcholine (EPC) and cholesterol (CH). Inorganic salts containing high valence counterions (HVCI) are encapsulated by the liposomes. The phase transition temperature of the liposome is at 38°C with 50 wt% addition of cholesterol. The encapsulation rate of liposomes reaches 85% for high valence anion (SO42−) and 55% for high valence cation (Ca2+). The liposomes are introduced into ceramic colloidal forming and dispersed in the suspension for identical charge with alumina particles at room temperature. The release of HCVI from the liposomes can coagulate the alumina suspension after heating at 38°C for 3 h, but the de‐moldable time is ~ 6–7 h. Dense ceramic products with relative density of above 98% and uniform microstructure can be prepared by this method without burnout process.